2012
DOI: 10.3402/polar.v31i0.11090
|View full text |Cite
|
Sign up to set email alerts
|

The oldest elasmosaurs (Sauropterygia, Plesiosauria) from Antarctica, Santa Marta Formation (upper Coniacian? Santonian–upper Campanian) and Snow Hill Island Formation (upper Campanian–lower Maastrichtian), James Ross Island

Abstract: Elasmosaurs are recorded for the first time in the Lachman Crags Member (Beta Member) of the Santa Marta Formation (lower Campanian) and in the Herbert Sound Member of the Snow Hill Island Formation (upper Campanian). These are the first elasmosaurids from James Ross Island, Antarctic Peninsula. These records greatly improve our knowledge of the taxonomic diversity of plesiosaurs of the Santa Marta Formation and Herbert Sound Member of the Snow Hill Island Formation, and extend the lower limit of the record of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 17 publications
0
21
0
2
Order By: Relevance
“…Late Cretaceous records of elasmosaurids (Sauropterygia, Plesiosauria) within the Weddellian Biogeographic Province (sensu Zinsmeister 1979; WBP hereafter) includes records from Antarctica, Argentina, Chile and New Zealand (Welles & Gregg 1971;Gasparini & Goñi 1985;Cruickshank & Fordyce 2002;Hiller et al 2005;Wilson et al 2005;Consoli & Stilwell 2009;O'Gorman 2012O'Gorman , 2013Otero et al 2012Otero et al , 2014aHiller et al 2014;O'Gorman et al 2014). In New Zealand, extensive descriptions of several proposed taxa have been presented since the late 19th century.…”
Section: Introductionmentioning
confidence: 98%
“…Late Cretaceous records of elasmosaurids (Sauropterygia, Plesiosauria) within the Weddellian Biogeographic Province (sensu Zinsmeister 1979; WBP hereafter) includes records from Antarctica, Argentina, Chile and New Zealand (Welles & Gregg 1971;Gasparini & Goñi 1985;Cruickshank & Fordyce 2002;Hiller et al 2005;Wilson et al 2005;Consoli & Stilwell 2009;O'Gorman 2012O'Gorman , 2013Otero et al 2012Otero et al , 2014aHiller et al 2014;O'Gorman et al 2014). In New Zealand, extensive descriptions of several proposed taxa have been presented since the late 19th century.…”
Section: Introductionmentioning
confidence: 98%
“…The Weddellian record of polycotylids remains meagre, in contrast with abundant elasmosaurid reports (Welles and Gregg, 1971;O'Gorman, 2012O'Gorman, , 2013Otero et al, 2014a,b). In Argentina only four polycotylid specimens have been collected (Gasparini and Spalletti, 1990;Gasparini and de la Fuente, 2000;Gasparini et al, 2003a;Salgado et al, 2007;O'Gorman et al, 2011;O'Gorman and Gasparini, 2013), and scarce fragmentary remains have been reported from New Zealand (Welles and Gregg, 1971;Wiffen and Moisley, 1986).…”
Section: Discussionmentioning
confidence: 83%
“…In Antarctica, the plesiosaur record is, to date present, restricted to elasmosaurids (Del Valle et al, 1977;Gasparini et al, 1984;Chatterjee and Small, 1989;Kellner et al, 2011;O'Gorman, 2012;O'Gorman et al, 2013;Otero et al, 2012;O'Gorman et al, 2015). However, a recent finding of isolated vertebrae described as belonging to an indeterminate plesiosaur by Kellner et al (2011), and later as possible related to Polycotylidae by O'Gorman (2012).…”
Section: Introductionmentioning
confidence: 85%
See 2 more Smart Citations